SOURCES OF COMPETITIVE ADVANTAGE IN THE DAIRY INDUSTRY: SUPPLY CHAIN MANAGEMENT PRACTICES - Maina, Charles; Njehia, Prof, Benard K.; Eric, Dr Bett Kiprotich (International Journal of Supply Chain Management, 2020)
Purpose: Ferocious competition in today's globalized markets and heightened customer expectations have pushed organisations into a constant search for new ways of securing competitive advantage. Against this backdrop, this paper sought to explore the effects of supply chain management (SCM) practices on the competitive advantage underpinned on resource-based view theory (RBV). Methodology: The study adopts descriptive and explanatory research design with purposive sampling and quantitative data collection methods through crossed ended questionnaires from 109 dairy co-operatives in Kenya. Data collected was organized and cleaned using both excel and statistical package for social scientist (SPSS). Additionally, partial least squares structural equation modelling (PLS-SEM) techniques were used to analyze data in SmartPLS version 3.2.9 software, and the results for both descriptive and inferential were presented in tables. Results: The findings show that SCM practices have a positive and significant (Î²= 0.736, t = 12.958, p=0.000) relationship with a competitive advantage. Further results show that supplier development has relatively high importance in explaining competitive advantage, followed by logistics management, information communication and technology, purchasing management, and customer relationship management. Specifically, the study recommends a close focus on the performance improvement of logistics management while monitoring the performance of the other four dimensions of SCM practices. Unique contribution to theory, practice and policy: The study provides insights into the practice of SCM to the managers in the dairy industry. Additionally, the study contributes to the policy by providing a framework for improving competitive advantage in the dairy industry. Furthermore, the study contributes to the literature of SCM practices in the dairy industry as well as the development and validation of the Resource-based View (RBV) theory.